Sustainable Manufacturing Practice: Knowledge Sharing by Malaysian SMEs - Fadhilah binti Mat Yamin; Norsiah binti Hami; Shafini binti Mohd Shafie; Mohd Razali bin Muhamad; Shahrun Nizam bin Abdul-Aziz (International Journal of Supply Chain Management, 2020)
Sustainable manufacturing has been widely studied and practise among manufacturing company around the world. This approach is one of the best approaches to reduce the environmental impact that produce during the manufacturing process. In Malaysia, this approach has been implemented in several SMEs company. This article will present four case studies that have been conducted on four SME company in Malaysia that had implemented SMP. The four companies were selected to share their knowledge and experience on the implementation, best practice and sustainability performance. The findings show that SMP has been well practice by those companies. All companies’ emphasis on reducing environmental and social issues by implementing a number of sustainable manufacturing practices such as cleaner production, eco-efficiency, employee-oriented sustainable practices, supplier-oriented sustainable practices, and customer-oriented sustainable practices. This finding can be used as a guideline for Malaysian SMEs in implementing the sustainable manufacturing practices in their organization.